If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 9)(4x + 7) = 0 Reorder the terms: (9 + 3x)(4x + 7) = 0 Reorder the terms: (9 + 3x)(7 + 4x) = 0 Multiply (9 + 3x) * (7 + 4x) (9(7 + 4x) + 3x * (7 + 4x)) = 0 ((7 * 9 + 4x * 9) + 3x * (7 + 4x)) = 0 ((63 + 36x) + 3x * (7 + 4x)) = 0 (63 + 36x + (7 * 3x + 4x * 3x)) = 0 (63 + 36x + (21x + 12x2)) = 0 Combine like terms: 36x + 21x = 57x (63 + 57x + 12x2) = 0 Solving 63 + 57x + 12x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(21 + 19x + 4x2) = 0 Factor a trinomial. 3((3 + x)(7 + 4x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(3 + x)' equal to zero and attempt to solve: Simplifying 3 + x = 0 Solving 3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + x = 0 + -3 x = 0 + -3 Combine like terms: 0 + -3 = -3 x = -3 Simplifying x = -3Subproblem 2
Set the factor '(7 + 4x)' equal to zero and attempt to solve: Simplifying 7 + 4x = 0 Solving 7 + 4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 4x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 4x = 0 + -7 4x = 0 + -7 Combine like terms: 0 + -7 = -7 4x = -7 Divide each side by '4'. x = -1.75 Simplifying x = -1.75Solution
x = {-3, -1.75}
| h(t)=-16t^2+60t+4 | | 2q+4-7+8q-q= | | 2x^2+11=-13 | | -2(v+3)+v=-30 | | -5p+32=12 | | 4g=692 | | 10t-12t=8 | | 3.5d+9.75=1+5.25d | | -2t+5=-7 | | a+34=57 | | -1(6x-2)=5(x+1) | | 4(10x+3)=-68 | | 3(c+7)-c= | | 4+8=-3 | | 6-x-x=17 | | 4a-3=9+a | | -19.4-15d+22d=44 | | cos(5x)+cos(5y)=0 | | 3(x-3)=2(6+x)1/2 | | y=x(2)-2x+3 | | 2k-10-7=8 | | 5(-2x-4)=97+3(4x+5) | | logx+log(4x-3)=1 | | 13=x^2-14x | | 32w-8w+21=69 | | 9y-15=-3(y+7) | | 22590-x=17500 | | 46t-9t+7t-40t+12=96 | | T(x)=2x^2+8x+6 | | 7x+12y=1 | | 62=5x | | 6p+14q= |